BNT162b2 and ChAdOx1 SARS-CoV-2 Post-vaccination Side-Effects Among Saudi Vaccinees - Alghamdi, Ahmed N.; Alotaibi, Mohammed I.; Alqahtani, Adel S.; Al Aboud, Daifullah; Abdel-Moneim, Ahmed S. (Frontiers in Medicine, 2021)
Background Vaccination against SARS-CoV-2 is important for reducing hospitalization and mortalities. Both Pfizer-BioNTech (BNT162b2) and the Oxford-AstraZeneca (ChAdOx1 nCoV-19) vaccines are used in Saudi Arabia and in many parts of the world. Post-vaccinal side effects were recorded, so we aimed to screen different complaints after vaccination among vaccinees in Saudi Arabia. Methods An online questionnaire was designed between May 10 and June 20, 2021, to screen the local, systemic, and allergic reactions post vaccination for vaccinees who received either one or two doses of the BNT162b2 vaccine or one dose of the ChAdOx1 vaccine. The number and percentage were recorded for each response and analysed using cross-tab and Chi square tests. The degree of the severity of post vaccination reactions were analysed using Roc curve. The cofactors that may affect the severity of post-vaccinal reactions including previous COVID-19 infection, age, sex, body mass index, and comorbidities were investigated. Results During our study, 4,170 individuals reported their responses: 2,145 received one dose of BNT162b2 of whom 456 received a second dose, and 1,569 received a single dose of ChAdOx1. The side effects were reported in 85.6% of BNT162b2 vaccinees and 96.05% of ChAdOx1 vaccinees who voluntarily responded to a survey about post-vaccination side effects. The side effects were more severe in BNT162b2 than ChAdOx1. ChAdOx1 vaccinees reported mild, moderate, severe and critical side effects in 30.13%, 28.62%, 29.73%, and 1.53%, respectively. In contrast, mild side effects were recorded among the majority of BNT162b2 vaccinees (63.92%) while moderate, severe, and critical side effects were 27.67%, 7.68% and 0.72%, respectively. Both local and systemic side effects were recorded more frequently in ChAdOx1 in comparison to BNT162b2 vaccinees. Palpitation was among the new systemic side effects reported in the current study in high frequency. Abnormal menstrual cycle (delaying/increase haemorrhages or pain) was also reported in 0.98% (18/1846) of Pfizer-BioNTech and 0.68% (7/1028) of ChAdOx1 vaccinees, while deep vein thrombosis was only reported in a single case vaccinated with BNT162b2 vaccine. Conclusion Both vaccines induced post-vaccinal side effects; however, ChAdOx1 induces a higher frequency of post-vaccinal systemic side effects than BNT162b2.